Marka kişiliğinin tüketici algısına etkisi ve bir uygulama - Yavuz, Elif (My University, 2004)
In order to be able to compete in the changing economy and survive in developing business environment, companies have to make the difference that will make them be recognized among others. This difference is brand name. Becoming a brand is a must for the companies in this era.However the Company in serch for brand, has to add her brand a personality in order to make the necessary difference. In this research, the rising concept brand personality is examined thoroughly and the blue-jean brands' personality perceptions in the eye of the consumers has been surveyed. The aim is to find out where the brand personality stands for the consumer and if it has any distinctive potential during decision process. After evaluating the survey results, we have focused on three different blue-jean brands. Then we tried to pinpoint the location of these three brands in the consumer's perception and the characteristics that represent these brands. The result of this research shows that these three blue-jean brands are indentified by different characteristics and are perceived differently by the consumers. During the recent years, brand personality has become an important value for the companies and it plays a significant role in the consumer decision process. Brand personality is a distinctive point that is added to the brand concept and it is obvious that becoming a real brand release on brand personality.

Son dönemde firmaların, ekonomik ve ticari hayattaki gelişmelere ve gün geçtikçe yoğunlaşan rekabet ortamına ayak uydurabilmeleri için öncelikle pazardaki diğer firmalar arasında ayırt edici özelliklere sahip olmaları gerekmektedir. Bu noktada firmaların kendilerine kattıkları ayırt edici değer marka'dır. Markalaşma artık firmaların vazgeçilmez bir unsuru haline gelmiştir. Ancak bir firmanın markası ile fark yaratabilmesi ve ben markayım diyebilmesi için markasına bir kişilik katması şart olmuştur. Yapmış olduğumuz bu çalışmada son yıllarda önemi oldukça artmış olan marka kişiliği kavramını ayrıntıları ile irdelemeye ve blucin markalarının tüketici algısındaki kişiliklerini incelemeye çalıştık. Amacımız tüketicinin gözünde marka kişiliği kavramının yerini ve ayırt edici olup olmadığını saptamaktı. Elde ettiğimiz verilerden yola çıkarak üç blucin markası üzerinde yoğunlaştık ve bu üç markanın tüketicinin algısında nerede olduğunu ve hangi kişilik özellikleri ile tanımlandığını saptamaya çalıştık. Yapmış olduğumuz bu çalışma sonucunda bu üç markanın birbirinden farklı kişilik özellikleri ile tanımlandığını ve tüketici algısında farklı yerlerde olduğunu saptadık. Özellikle son yıllarda firmalar açısından önemli bir değer haline gelen ve tüketicinin tercihinde önemli bir rol oynayan marka kişiliği, marka kavramına katılan ayırt edici özelliktir ve gerçek bir marka olabilmenin yolu marka kişiliği kavramından geçmektedir.
Keywords: Ticari Marka; Tüketici Tercihleri; Tüketiciler